Constitutionality of Indigenous Law Communities in the Perspective of Sociological Jurisprudence Theory - Sapto Hermawan; Muhammad Rizal; Farchana Haryumeinanda; Yella Hasrah Cahya Oktiviasti (Jurnal Jurisprudence, 2021)
Objective: This study aims to determine the existence and position of customary law communities in Indonesia and to examine how the constitutionality of customary law in Indonesia is from the perspective of sociological jurisprudence.Method: The method used in this research is a normative juridical approach which is focused on examining various kinds of laws and regulations and theoretical concepts. In this study, researchers examine the 1945 Constitution of the Republic of Indonesia, Law No. 41 of 1999 concerning Forestry, until the Constitutional Court Decision No. 35/PUU-X/2012 concerning Customary Forests, while for the theoretical conceptual approach the researcher examines the concept of customary law, and the concept of customary law communities and their relation to the concept of sociological jurisprudence.Finding: The results of the study show that the concept of customary law as part of the State of Indonesia when viewed from the perspective of Sociological Jurisprudence as a law that grows and lives in society. Juridically, the traditional rights of indigenous and tribal people are also constitutional rights because they are stated in the constitution, as emphasized in Article 18 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, in relation to sociological jurisprudence, the new positive law will be effective if its implementation is appropriate and contains the principles that live in society. The gravity of the law is not found from the law itself, but from the community. So it is proper that the content and protection and recognition related to the existence of customary law are regulated in laws and regulations.Usage: This article can provide input for policy makers, especially the central and local governments regarding the urgency of the formation of a draft law on customary law communities, where the law is expected to provide legal protection to the rights of indigenous peoples because indigenous peoples have existed long before the Republic of Indonesia was formed so that its existence was recognized in the Constitution.Novelty: Legal certainty regarding the constitutionality of customary law in Indonesia is particularly important for indigenous peoples, and extremely useful for recognizing the existence of indigenous peoples in Indonesia. Determining the constitutionality of customary law in Indonesia in the perspective of sociological jurisprudence will ensure legal certainty in relation to customary law, which until now there are no explicit rules governing customary law in Indonesia.